Molecular Pathogenic Mechanisms of Hypomyelinating Leukodystrophies (HLDs) - Tomohiro Torii; Junji Yamauchi (Neurology International, 2023)
Hypomyelinating leukodystrophies (HLDs) represent a group of congenital rare diseases for which the responsible genes have been identified in recent studies. In this review, we briefly describe the genetic/molecular mechanisms underlying the pathogenesis of HLD and the normal cellular functions of the related genes and proteins. An increasing number of studies have reported genetic mutations that cause protein misfolding, protein dysfunction, and/or mislocalization associated with HLD. Insight into the mechanisms of these pathways can provide new findings for the clinical treatments of HLD.